Macrolides sensitize EGFR-TKI-induced non-apoptotic cell death via blocking autophagy flux in pancreatic cancer cell lines - MUKAI, SHUNTARO; MORIYA, SHOTA; HIRAMOTO, MASAKI; KAZAMA, HIROMI; KOKUBA, HIROKO; CHE, XIAO-FANG; YOKOYAMA, TOMOHISA; SAKAMOTO, SATOSHI; SUGAWARA, AKIHIRO; SUNAZUKA, TOSHIAKI; ŌMURA, SATOSHI; HANDA, HIROSHI; et al. (International journal of oncology, 2016)
Pancreatic cancer is one of the most difficult types of cancer to treat because of its high mortality rate due to chemotherapy resistance. We previously reported that combined treatment with gefitinib (GEF) and clarithromycin (CAM) results in enhanced cytotoxicity of GEF along with endoplasmic reticulum (ER) stress loading in non-small cell lung cancer cell lines. An epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) such as GEF induces autophagy in a pro-survival role, whereas CAM inhibits autophagy flux in various cell lines. Pronounced GEF-induced cytotoxicity therefore appears to depend on the efficacy of autophagy inhibition. In the present study, we compared the effect on autophagy inhibition among such macrolides as CAM, azithromycin (AZM), and EM900, a novel 12-membered non-antibiotic macrolide. We then assessed the enhanced GEF-induced cytotoxic effect on pancreatic cancer cell lines BxPC-3 and PANC-1. Autophagy flux analysis indicated that AZM is the most effective autophagy inhibitor of the three macrolides. CAM exhibits an inhibitory effect but less than AZM and EM900. Notably, the enhancing effect of GEF-induced cytotoxicity by combining macrolides correlated well with their efficient autophagy inhibition. However, this pronounced cytotoxicity was not due to upregulation of apoptosis induction, but was at least partially mediated through necroptosis. Our data suggest the possibility of using macrolides as 'chemosensitizers' for EGFR-TKI therapy in pancreatic cancer patients to enhance non-apoptotic tumor cell death induction.